Simon Dalby: A Pioneer in International Relations
XIV, 266 p. 6 illus., 5 illus. in color.
Keywords: This book profiles Simon Dalby’s academic contributions in the fields of critical geopolitics, environmental security and the intersection of international relations and the Anthropocene. It includes reprints of key essays that highlight innovations in critical thought at the intersections between geopolitics, environment and security. Starting with an analysis of American reconstructions of the Soviet threat in the 1970s, an early contribution to the emerging field of critical geopolitics, subsequent papers focus on the emergent formulations of environmental security in the aftermath of the Cold War and the environmental costs of globalization. Focusing on the implicit geographical framing in discourses of globalization offered a critique that extended the ambit of critical geopolitics to grapple with the issues of environmental security and the rising concern with climate change as well as the political identities invoked in that debate. In the aftermath of 9/11, similar arguments about contextualization applied to the American global war on terror and the revival of discussions of empire and its geographies, both in arguments for invading Iraq, as well as the wider discussions in policy discourse and popular culture. Simultaneously, the emergence of earth system science and the concept of the Anthropocene offered another way to highlight the dangers of fossil fueled economic activities. The necessity of fundamentally rethinking the premises of security policy in light of this recontextualization is emphasized in more recent contributions on climate security and the current ecological crisis. Critical geopolitics Environmental security Global war on terror Firepower in the Anthropocene.